Staff perspectives of relationships in aged care: A qualitative approach. (15th March 2016) - Jones, Cindy; Moyle, Wendy
Abstract : Aim: To explore aged care staff perceptions and experience of their relationships with co‐workers, older people and families via pragmatic exploratory interviews. Methods: Thirty‐nine direct care staff from seven residential age care facilities and 12 community organisations were interviewed. Results: Staff felt that their capacity to develop therapeutic relationships with older people and families was impeded by care tasks and concerns regarding professional boundaries. Positive relationships between staff–family and staff–staff are hindered by staff perceptions of undue care demands, high family expectations, and staff–staff conflict within a hierarchical context and between work shifts. Conclusion: A relationship‐centred approach to care as well as staff training and education should be encouraged to assist the development of therapeutic relationships and the management of professional boundaries.